Internal eradicability for an epidemiological model with diffusion - Sebastian Aniţa; Bedreddine Ainseba (Mathematical Biosciences and Engineering)
This work is concerned with the analysis of the possibility for eradicating a disease in an infected population. The epidemiological model under study is of SI type with diffusion. We assume the policy strategy acting on the infected individuals over a subset of the whole spatial territory. Using the framework of nonlinear reaction-diffusion equations, and spectral theory of linear differential operators, we give necessary conditions and sufficient conditions of eradicability.